“ҲИБАТУЛ-ҲАҚОЙИҚ”ДАГИ АЙРИМ ЎЗЛАШМАЛАР ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
In this article semes and etymology of some derived words used in “Hibatul haqoyiq”  by Ahmad Yugnakiy are expounded. Lexical items on the derived layer of words in “Hibatul haqoyiq” are comparatively analysed with old Turkic language and the words of  Karakhaniy period as well XIV century sources.